1999
DOI: 10.1017/s0950268898001782
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoea prevention in Bolivia through point-of-use water treatment and safe storage: a promising new strategy

Abstract: A novel water quality intervention that consists of point-of-use water disinfection, safe storage and community education was field tested in Bolivia. A total of 127 households in two periurban communities were randomized into intervention and control groups, surveyed and the intervention was distributed. Monthly water quality testing and weekly diarrhoea surveillance were conducted. Over a 5-month period, intervention households had 44% fewer diarrhoea episodes than control households (P = 0.002). Infants < 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(151 citation statements)
references
References 15 publications
4
143
2
2
Order By: Relevance
“…The lack of health impact in the context of successful treatment of stored drinking water was not consistent with results of previous studies of other chlorine-based, point-of-use water treatment interventions. 7,9,[12][13][14][15][16] There are several possible explanations for the observed lack of health impact. First, it is possible that disinfected stored water does not prevent diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of health impact in the context of successful treatment of stored drinking water was not consistent with results of previous studies of other chlorine-based, point-of-use water treatment interventions. 7,9,[12][13][14][15][16] There are several possible explanations for the observed lack of health impact. First, it is possible that disinfected stored water does not prevent diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, a number of household water treatment technologies have been developed, tested, and disseminated to protect the health of populations lacking access to safe water. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] One of these household water treatment technologies is sodium dichloroisocyanurate (NaDCC) tablets, an alternative to sodium hypochlorite (NaOCl) solution, which is produced and distributed in many countries for water treatment. 17 Both NaDCC tablets and NaOCl solution disinfect water by releasing free available chlorine in the form of hypochlorous acid, which is an effective microbicide against a wide range of bacteria, viruses, and parasites.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]41 These risk factors were on water, sanitation, hygiene, and knowledge of the causes of childhood diarrheal disease and prevention. All of these variables were obtained from the baseline KPC survey administered to the primary caregiver in each household.…”
Section: Methodsmentioning
confidence: 99%
“…In Cochabamba, Bolivia, the site of this study, the most recent government survey from 2008 reported a diarrhea prevalence of 36.2% for children 5 years of age for the department. 2 Previous studies have identified risk factors for diarrhea such as younger age, 3,4 male gender, 4,5 early weaning, 5-8 seasonal patterns, 5,7,9 low maternal education, 5,9,10 lack of piped water supply, 9,[11][12][13][14][15] poor water-storage practices, 9,14-18 younger maternal age, 11,12 lack of hand washing with soap by caregiver, 18,19 poor sanitation, 9,16,18,20,21 visible feces in the yard, 4 indiscriminate disposal of child feces, 17 unsatisfactory garbage disposal, 11 shorter boiling time, 13 using water from cistern trucks, 13 and not treating water in the home. 13 In a recent multisite study it was found that rotavirus was the most common cause of moderate to severe diarrhea in children 0-23 months of age, and shigellosis for the age group 24-59 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, the Centers for Disease Control and Prevention (CDC) and Pan American Health Organization (PAHO)/WHO developed the Safe Water System (SWS) to prevent diarrhoea through the promotion of household water treatment, safe water storage and behaviour change communications [4]. Point-of-use water treatment and safe water storage, has been shown to reduce diarrhoea risk by 25-85 %, depending on the population, setting, and other factors [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%